PENGHAKIMAN MAHKAMAH SYARIAH MALAYSIA: ANALISIS KES-KES TERPILIH: Shariah Court Judgement in Malaysia: An Analysis of Selected Cases - Buang, Ahmad Hidayat; Mat Hussin, Mohd Norhusairi; Daud, Mohd Zaidi (Jurnal Syariah, 2022)
Article’s objective is to analyse decisions of the Shariah Courts in Malaysia from the perspective of case law reporting on its judgment with particular interest to observe the tendency, challenges and problems faced by these courts while delivering judgement. Analysis is made to cases reported in the Jurnal Hukum published by Department of Shariah Judiciary Malaysia (JKSM) and Syariah Law Reports published by LexisNexis in the year 2012 as sampling. From the cases analysed it was found that the Shariah judges are prepared to make orginal interpretation in matters relating to procedure but would rely normatively on the Islamic Shariah in substatantive matters, although the provisions of the law allow the court flexibility to be innovative. It is also found that the courts in the judgment include additional discussion to the main issue or question of the case which is probably not relevant. Shariah judges also follow and refer the decisions or interpretation of cases reported and this solidifies the position that Shariah Courts do practice the principle of binding precedent.